The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702291
|View full text |Cite
|
Sign up to set email alerts
|

Debating Poverty Porn on Twitter

Abstract: This paper presents an empirical investigation of how people appropriated Twitter for socio-political talk in response to a television (TV) portrayal of people supported by state welfare and benefits. Our findings reveal how online discussion during, and in-between, TV broadcasts was characterised by distinctly different qualities, topics and user behaviours. These findings offer design opportunities for social media services to (i) support more balanced real-time commentaries of politically-charged media, (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…This also means that viewers may tend to conform to the popular opinions seen on Twitter, although this effect diminishes when the topic becomes very politically polarising [10]. Temporal effects also influence the online discourse: research around a politically charged documentary showed that during broadcast viewers tended to post judgemental content, whereas post-broadcast, the Tweets tend to be more defensive and appreciative [8].…”
Section: Second Screensmentioning
confidence: 99%
“…This also means that viewers may tend to conform to the popular opinions seen on Twitter, although this effect diminishes when the topic becomes very politically polarising [10]. Temporal effects also influence the online discourse: research around a politically charged documentary showed that during broadcast viewers tended to post judgemental content, whereas post-broadcast, the Tweets tend to be more defensive and appreciative [8].…”
Section: Second Screensmentioning
confidence: 99%
“…In a study exploring the effect of combining political television with social media content, it was discovered that viewers have the tendency to conform to the opinions they see expressed through social content, although the effect was less pronounced when the footage was about polarising political issues like gun regulation [7]. Another example is a study into the use of Twitter around a politically charged program called Benefits Street, which looks into the lives of British benefits recipients [5]. The study discovered that during air time the content generated on Twitter tended to be abusive and judgemental, whereas between the programs viewers of the program posted much more appreciating, defending and contesting content [5].…”
Section: Background Second Screensmentioning
confidence: 99%
“…Another example is a study into the use of Twitter around a politically charged program called Benefits Street, which looks into the lives of British benefits recipients [5]. The study discovered that during air time the content generated on Twitter tended to be abusive and judgemental, whereas between the programs viewers of the program posted much more appreciating, defending and contesting content [5].…”
Section: Background Second Screensmentioning
confidence: 99%
“…We are particularly interested in how these issues are manifested around televised political debates, where viewers utilise their personal devices or second screens to gauge the opinions of the public, share their own views, or as a form of entertainment [20]. Within this work we adopt a broad definition of second screens as devices used alongside television for activities that are both related and unrelated to the broadcast [7,11,14,18,39]. Political debates are a key point in election campaigns, where social media activity is particularly high.…”
Section: Introductionmentioning
confidence: 99%
“…Political debates are a key point in election campaigns, where social media activity is particularly high. Previous research has explored how Twitter is being used in this context [2,7,21], what motivates viewers to use their devices [20], and the effect of social media on opinion formation during debates [33,34]. What remains is to identify directions for the development of appropriate second screen tools that cater to viewers' needs and address the current issues with political discourse online more broadly.…”
Section: Introductionmentioning
confidence: 99%